Answer:
a) 0.0019
b) 0.0913
c) 9.13%
Step-by-step explanation:
We are given the following information in the question:
[tex]Q(t)=0.0019(2.22)^{-3t}[/tex]
The standard form of exponential function is
[tex]f(t) = ab^{t}[/tex]
where a is the initial amount and b is the base.
Rewriting the the given function, we have:
[tex]Q(t)=0.0019(2.22)^{-3t}\\Q(t)=0.0019((2.22)^{-3})^t\\Q(t)=0.0019(0.0913)^t[/tex]
a) Initial Value
Putting t = 0, we get,
[tex]Q(0)=0.0019(0.0913)^0 = 0.0019[/tex]
a = 0.0019
b) Growth factor
Comparing, we get, b = 0.0913
c) Growth rate
[tex]\text{Growth factor}\times 100\% = 0.0913\times 100\% = 9.13\%[/tex]